PENERAPAN MODEL PEMBELAJARAN KIK-IRMA DENGAN MENGGUNAKAN MEDIA CANVA DALAM MENULIS TEKS BIOGRAFI DI KELAS X SMA - Rahmi, Aulia; Irma Suryani; Rahmawati (STKIP Subang, 2026)
This study aims to describe the application of the KIK-IRMA learning model using Canva as a medium for teaching biographical writing to tenth-grade high school students. This study employed a qualitative approach with a case study method. The subjects consisted of Indonesian language teachers and 36 tenth-grade E3 students at SMA Negeri 1 Jambi City. Data collection techniques included participant observation, semi-structured interviews, and documentation. Data analysis employed the Miles and Huberman model, which encompasses data reduction, data presentation, and conclusion drawing. The results showed that the application of the KIK-IRMA learning model combined with Canva created an interactive, collaborative, and creative learning environment. The use of Canva helped students organize biographical information visually and systematically, making it easier for them to develop ideas and write coherent biographical texts. Furthermore, the KIK-IRMA model encouraged students to actively discuss, explore information, and produce biographical posters in groups and individual biographical texts. The assessment results for 36 student works showed that 25 students (69%) received excellent grades, 6 students (16.6%) received good grades, and 5 students (13.8%) received fair grades, with no students receiving poor grades. These findings suggest that the application of the KIK-IRMA learning model combined with Canva can help improve students' writing skills, particularly in composing biographical texts coherently, systematically, and in accordance with linguistic rules. Therefore, the KIK-IRMA model, aided by Canva, can be an alternative, innovative learning strategy for Indonesian language instruction on writing biographical texts.